Apigenin promotes melanogenesis and melanosome transport through the c-KIT/Raf-1/MAPK/CREB pathway in HEMCs - Lv, Jinpeng; Meng, Duo; Zhang, Huansha; Xu, Wenhui; An, Xiaohong; Yin, Chuanwei; Zou, Kun; Gao, Rongyin (Frontiers in Pharmacology, 2025)
IntroductionApigenin, a natural flavonoid with well-established antioxidant, anticancer, and anti-inflammatory activities, has recently attracted attention for its pigmentation-promoting effects. However, the underlying molecular mechanisms driving its melanogenic activity remain incompletely understood.MethodTo investigate apigenin‘s effects on melanogenesis, human epidermal melanocytes (HEMCs), zebrafish embryos, and human skin explants were treated with apigenin. Melanin content, dendrite formation, and melanosome maturation were evaluated using spectrophotometry and transmission electron microscopy. Key signaling molecules and proteins involved in melanogenesis and melanosome transport were assessed by Western blotting and immunohistochemistry. The role of the c-KIT receptor was further explored through pharmacological inhibition and genetic knockdown approaches. Functional pigmentation was evaluated by assessing UVB-induced DNA damage markers.ResultsApigenin (10 μM) significantly increased melanin production by 1.8-fold in HEMCs, enhanced dendritic morphology, and promoted stage III–IV melanosome formation. Mechanistically, apigenin induced melanogenesis independently of the MC1R/cAMP/PKA pathway by directly binding to the c-KIT receptor, activating the Raf-1/ERK/RSK cascade, and upregulating MITF. This led to elevated expression of tyrosinase, TRP-1, TRP-2, and melanosome transport proteins Rab27a and Cdc42. Inhibition or knockdown of c-KIT abrogated these effects. In vivo, apigenin restored pigmentation in PTU-induced depigmented zebrafish and increased melanin content by 1.3-fold in human skin explants. Histological analysis confirmed effective melanin transfer to keratinocytes. Additionally, apigenin-treated skin showed reduced UVB-induced DNA damage, indicating enhanced photoprotection.DiscussionThese findings demonstrate that apigenin stimulates melanogenesis through a novel c-KIT-dependent signaling pathway and promotes functional pigmentation with photoprotective benefits. Given its dietary origin, favorable safety profile, and multifaceted mechanisms, apigenin holds promise as a therapeutic agent for vitiligo and a natural pigmentation enhancer for dermatological use.